Efektivitas Penggunaan Media Pembelajaran Flashcard dalam Keterampilan Menulis Aksara Sunda Siswa Madrasah Ibtidaiyah - Zakiyah, Suci (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
The ability to write Sundanese script has received serious attention because it is related to the preservation of intangible cultural heritage, many of the MI level students who cannot write Sundanese script do not even know what Sundanese script is like. Implementation of learning to write Sundanese script in MI can be carried out using flashcard learning media. The formulation of the problem in this study in general is "How is the effectiveness of using flashcard learning media in writing skills in Sundanese script for MI students?". The purpose of this study was to determine the effectiveness of the use of flashcard learning media in the writing skills of the MI students in Sundanese script. The research to be carried out is a qualitative research with data collection techniques of observation, questionnaires, and tests. The instruments used in this study were test sheets and observation sheets. The form of this research is qualitative research, the population and sample in this study are fifth grade students at MI Miftahul Huda, Tasikmalaya City. The results of this study indicate that many students find it helpful in learning to write, as evidenced by 90% of students who can write with a guide and 65% of students can write a guide without a guide, but 95% of students can write their identity with Sundanese script without looking at the guide.